Leverage? : What Leverage? A Deep Dive into the U.S. Flow of Funds in Search of Clues to the Global Crisis - Bayoumi, Tamim; Bhatia, Ashok (Washington, D.C. : International Monetary Fund, 2012)
This paper questions the view that leverage should have forewarned us of the global financial crisis of 2007-09, pointing to several gearing indicators that were neither useful portents of the onset of the crisis nor of its ferocity. Instead it shows, first, that the use of ill-suited collateral in the secured funding operations of U.S.-based investment banks was the fatal link between the collapse of structured finance and the global malfunction of funding markets that turbocharged the downdraft; and, second, that this insight (and others) can be decrypted from the Flow of Funds Accounts of the United States.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet